Engineering Applications of Biochar 2017
DOI: 10.5772/intechopen.68221
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Municipal Solid Wastes into Biochar through Hydrothermal Carbonization

Abstract: In this study, the hydrothermal treatment of municipal solid wastes (MSWs) for the production of biochar as a renewable solid fuel was investigated. The properties of surrogate MSWs and mixtures of newspaper and vegetables were greatly improved by hydrothermal treatment and were similar to those of coal-like fuel substances. Hydrothermal treatment increased the calorific value, the fixed carbon, and carbon contents. The composition of the major biomass components of MSW was found to affect the alternation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Tekin et al [237] conducted experiments and determined the HHV of acetone extract as 24.4, and of ether extract as 22.9 MJ kg −1 d.m. Kim et al [238] report cellulose LHV to be 16.5, hemicellulose to be 13.9, and lignin to be 20.4 MJ kg −1 d.m., whereas according to Ma et al [239], the respective values are: 15.4, 14.6, and 24.5 MJ kg −1 d.m. A similar analogy can be sought in the higher LHV for branches compared to wood, caused by the (diverse) bark content in the former.…”
Section: Higher Heating Value (Hhv)mentioning
confidence: 99%
“…Tekin et al [237] conducted experiments and determined the HHV of acetone extract as 24.4, and of ether extract as 22.9 MJ kg −1 d.m. Kim et al [238] report cellulose LHV to be 16.5, hemicellulose to be 13.9, and lignin to be 20.4 MJ kg −1 d.m., whereas according to Ma et al [239], the respective values are: 15.4, 14.6, and 24.5 MJ kg −1 d.m. A similar analogy can be sought in the higher LHV for branches compared to wood, caused by the (diverse) bark content in the former.…”
Section: Higher Heating Value (Hhv)mentioning
confidence: 99%
“…HC y (wt%) is the solid yield of HTC processes and is calculated by (1), where m HC (g) is the mass of HC and m i (g) is the mass of the initial feedstock (15 g of raw scales):…”
Section: Hydrothermal Carbonization Processmentioning
confidence: 99%
“…Many investigations into the development of alternative resources and renewable energy are aimed at addressing the growing demand for energy as well as the continuing rise in energy prices and the persistent shortage of hydrocarbon resources [1]. Switching to a scenario with a greater share of renewable energies involves the use of biomass since this resource is certainly effective in providing energy in diverse forms such as heat, electricity, fuel for transportation, and so on depending on the thermochemical process used.…”
Section: Introductionmentioning
confidence: 99%
“…The mixture of different feedstocks to add in the HTC process called co-HTC is an innovative method for treating different wastes at the same time. A pilot-scale plant involving a reactor volume of 200 L was used to perform the co-HTC process of a 20 kg mixture of paper waste and food waste according to the optimal condition at the lab scale [41]. The results indicated that the mixture ratio with the higher mixture ratio of paper waste significantly increased the carbon content and calorific value of hydrochar.…”
Section: Upscaling Case Of Htc and Challengesmentioning
confidence: 99%